Design and Analysis of Automotive Air-Conditioning System - Lenin Rakesh, N.; Anbazhagan, G.; Jayabal, Suriyakumar (International Journal of Psychosocial Rehabilitation, 2019)
Automotive air conditioning systems are traditionally designed by choosing the right components from the upholstery of available component sizes and specifications, thereby expecting such chosen components to meet the heat load estimations in the automobile. This is almost a complete practical approach of choosing components, forming a cycle, and testing them to ensure desired results. If often happens, that a certain design parameter, say the size of a component, has to be modified to arrive at optimized results. This would again require new prototypes and testing, which is both time-consuming and expensive. In this project, a simulation methodology is formed and executed, which provides a quicker estimation of air conditioning performance, thereby avoiding unnecessary loss of time and money. The work is based on assigning a suitable functional relationship and performance model of each component, thereby forming a one-dimensional analysis cycle. The modelling consists in first describing the characteristics of the various components of the system and the study of their characteristics. Major components like compressors, heat exchangers, and expansion values are discussed in detail. Suitable functional relations are used in the mathematical description of these components. The component sub-models are integrated to form a holistic or a cycle simulation model. The output of the cycle is attempted to be plotted on a time axis to deduce the cooling pattern of the automobile.